Effect of particle size and tapioca starch content on performance of the rice husk and red bean skin briquettes - Anggraeni, S. (Taylor's University, 2021)
This study investigated effects of particle size and the amount of tapioca starch adhesive on briquettes performance. Experiments were carried out by mixing microparticles of rice husk (2000-500; 250-125; and 100-74 Î¼m), microparticles of kidney bean shells (2000-500; 250-125; and 100-74 Î¼m), and binders (20, 30, 40, and 50). In the experiments, the rice husk and red bean skin was cleaned, dried, and put in an electrical oven at 200Â°C for 2 hours. The waste from rice husks and red bean skin was then separated according to the particle size and processed into briquettes with the same pressure (18.59 N/cm3). Several series of tests were carried out such as compressed density, relaxed density, relaxation ratio, percentage of moisture content, water boiling test, combustion rate, specific fuel consumption, and water resistance index. The results showed that briquettes have a good quality when using small particles (100-74 Î¼m) with a binder concentration of 50. The small particles have large surface area, and the high concentration of binders makes the bonds between the particles hold together strongly. For the briquettes with large particles (2000-500 Î¼m), the good quality of briquette was obtained when using a binder concentration of 20. The large particles and low binder concentration make the porosity of the briquette higher. Based on the results, combination of the rice husk and red bean skins have good characteristics, and the best was obtained when using particle sizes of 100-74 Î¼m with adhesive concentrations of 50. This study demonstrated the important of several parameters for enhancing briquette performance. Â© School of Engineering, Taylorâs University